Mass-selective and ice-free electron cryomicroscopy protein sample preparation via native electrospray ion-beam deposition. Issue 4 (6th August 2022) - Esser, Tim K; Böhning, Jan; Fremdling, Paul; Agasid, Mark T; Costin, Adam; Fort, Kyle; Konijnenberg, Albert; Gilbert, Joshua D; Bahm, Alan; Makarov, Alexander; Robinson, Carol V; Benesch, Justin L P; et al.
Abstract: Despite tremendous advances in sample preparation and classification algorithms for electron cryomicroscopy (cryo-EM) and single-particle analysis (SPA), sample heterogeneity remains a major challenge and can prevent access to high-resolution structures. In addition, optimization of preparation conditions for a given sample can be time-consuming. In the current work, it is demonstrated that native electrospray ion-beam deposition (native ES-IBD) is an alternative, reliable approach for the preparation of extremely high-purity samples, based on mass selection in vacuum. Folded protein ions are generated by native electrospray ionization, separated from other proteins, contaminants, aggregates, and fragments, gently deposited on cryo-EM grids, frozen in liquid nitrogen, and subsequently imaged by cryo-EM. We demonstrate homogeneous coverage of ice-free cryo-EM grids with mass-selected protein complexes. SPA reveals that the complexes remain folded and assembled, but variations in secondary and tertiary structures are currently limiting information in 2D classes and 3D EM density maps. We identify and discuss challenges that need to be addressed to obtain a resolution comparable to that of the established cryo-EM workflow. Our results show the potential of native ES-IBD to increase the scope and throughput of cryo-EM for protein structure determination and provide an essential link between gas-phase and solution-phase protein structures.